2021
DOI: 10.1073/pnas.2108959118
|View full text |Cite
|
Sign up to set email alerts
|

Functional alterations in cortical processing of speech in glioma-infiltrated cortex

Abstract: Recent developments in the biology of malignant gliomas have demonstrated that glioma cells interact with neurons through both paracrine signaling and electrochemical synapses. Glioma–neuron interactions consequently modulate the excitability of local neuronal circuits, and it is unclear the extent to which glioma-infiltrated cortex can meaningfully participate in neural computations. For example, gliomas may result in a local disorganization of activity that impedes the transient synchronization of neural osc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 61 publications
(73 reference statements)
0
31
0
Order By: Relevance
“…This is all the more relevant since preserved and dysfunctional activity patterns measured intraoperatively around the tumor during task performance have been shown to be relevant for cognitive processes. 9 Previous studies have speculated on the role of epilepsy in promoting activity-dependent tumor growth, 4,50 and seizures were found to directly increase the neurogliomal calcium transients leading to tumor growth and infiltration. Finally, we did not find LENS values to have predictive power in terms of PFS or OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is all the more relevant since preserved and dysfunctional activity patterns measured intraoperatively around the tumor during task performance have been shown to be relevant for cognitive processes. 9 Previous studies have speculated on the role of epilepsy in promoting activity-dependent tumor growth, 4,50 and seizures were found to directly increase the neurogliomal calcium transients leading to tumor growth and infiltration. Finally, we did not find LENS values to have predictive power in terms of PFS or OS.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, there are indications that healthy and pathological activity in the (peri)tumoral region are interdigitated during cognitive performance in these patients. 9 This complex bidirectional interaction between the brain and glioma that informs both tumor and patient behavior has sparked the relatively new field of 'cancer neuroscience', aiming to elucidate how this crosstalk may inform understanding and treatment of glioma. 10,11 A potential implication of this line of research pertains to the relevance of 'intrinsic' brain activity, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…recently demonstrated the extent to which glioma‐infiltrated cortex can meaningfully participate in neural computations. [ 40 ] Using subdural electrocorticography, they demonstrated that glioma‐infiltrated cortex engaged in synchronous activity during task performance in a manner similar to normal‐appearing cortex but recruited a diffuse spatial network. However, neuronal activation within glioma‐infiltrated language areas suffered from a loss of information storage capacity (entropy).…”
Section: Neuroplasticity Mechanisms In Gliomamentioning
confidence: 99%
“…Brain cancers exist within the context of non-neoplastic neurons and glia. Neoplastic cell proliferation may therefore directly impact neurological and cognitive processes [1]. The neurological and cognitive implications of central nervous system (CNS) tumors have become an important area of investigation [2].…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…Longitudinal cognitive and behavioral testing is underway at many institutions to understand symptom and disease trajectory. Cognition testing, however, may be obtained (1) as part of standard of care patient management, (2) for investigational only purpose, or (3) collected for clinical purposes yet maintained in a registry for investigational use. Challenges such as managing patient anxieties, deciding on the optimal time to administer a behavioral task, task duration, and consenting aphasic and severely cognitively impaired patients each require special consideration [3,4].…”
Section: Introduction and Overviewmentioning
confidence: 99%